PENYULUHAN TENTANG PENCEGAHAN HIPERTENSI DENGAN MENGHINDARI FAKTOR RISIKO KEPADA WARGA BINAAN PEMASYARAKATAN DI LAPASKELAS II B PADANGSIDIMPUAN TAHUN 2018 - Nefonavratilova Ritonga; Nurelilasari Siregar (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
Cardiovascular disease according to the 1992 AND 1995 Household Health Survey (SKRT) is the biggest cause of death in Indonesia, one of which is hypertension (Yunis, 2003). This shows how serious the problem of increasing hypertension that is happening in Indonesia is, if not followed by an increase in health knowledge related to changes in people's behavior to prevent hypertension by staying away from hypertension risk factors. So based on the above problems, we intend to hold counseling on the prevention of hypertension by avoiding risk factors for the Correctional Center in Padangsidimpuan Class II B Prison in 2018. Extension activities were very enthusiastic in response to the assisted residents, seen from several assisted residents who asked related questions